2011
DOI: 10.3109/09638237.2011.562261
|View full text |Cite
|
Sign up to set email alerts
|

Navigating uncharted waters? How international experience can inform the funding of mental health care in England

Abstract: New payment systems must account for the economic incentives they embody, and appropriate adjustments for variations in length of stay are essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 10 publications
0
32
0
1
Order By: Relevance
“…Indeed, this applicability is particularly limited given that only a few other countries (eg, Australia, New Zealand, Canada, the Netherlands, Norway, USA) have made progress implementing mental health payment systems, using heterogeneous clustering and resource distribution methodologies. 23 Fourth, the Figure 2 Frequency of HSU prediction by variable category. HSU, health service utilisation; frequencies were obtained by counting some studies various times for one variable category; for interventions, the count concerned the prediction of decreased HSU.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…Indeed, this applicability is particularly limited given that only a few other countries (eg, Australia, New Zealand, Canada, the Netherlands, Norway, USA) have made progress implementing mental health payment systems, using heterogeneous clustering and resource distribution methodologies. 23 Fourth, the Figure 2 Frequency of HSU prediction by variable category. HSU, health service utilisation; frequencies were obtained by counting some studies various times for one variable category; for interventions, the count concerned the prediction of decreased HSU.…”
Section: Methodological Considerationsmentioning
confidence: 99%
“…7 Achieving homogeneity within clusters is considered essential to ensure that PbR will not introduce financial risk for providers. 8,9 This was the primary reason why similar approaches to payment were not implemented for mental health services in the USA, Australia or New Zealand. [9][10][11] Similarly, initial cost analyses in the UK demonstrated that homogeneity within clusters was 'unacceptably low' and that providers vary in their resource utilisation much more than what could be explained by differences in their case-load.…”
Section: Discussionmentioning
confidence: 99%
“…At present, NHS mental health services are primarily funded through block contracts agreed between commissioners and providers of care, or on the basis of levels of existing 'inputs' such as the number of beds (Mason 2011a). This method of financing, often termed retrospective reimbursement, offers little incentive for providers to deliver an efficient level of care (Mason 2011a) because it does not encourage them to control costs or increase output (activity levels).…”
Section: Retrospective Reimbursementmentioning
confidence: 99%
“…This method of financing, often termed retrospective reimbursement, offers little incentive for providers to deliver an efficient level of care (Mason 2011a) because it does not encourage them to control costs or increase output (activity levels). This is because an agreed fixed sum is paid regardless of the number of patients treated.…”
Section: Retrospective Reimbursementmentioning
confidence: 99%